2016
DOI: 10.1097/qai.0000000000001062
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Cash Transfers to Increase Retention in PMTCT Care, Antiretroviral Adherence, and Postpartum Virological Suppression: A Randomized Controlled Trial

Abstract: Background:Novel strategies are needed to increase retention in prevention of mother-to-child HIV transmission (PMTCT) services. We have recently shown that small, incremental cash transfers conditional on attending clinic resulted in increased retention along the PMTCT cascade. However, whether women who receive incentives to attend clinic visits are as adherent to antiretrovirals (ARV) as those who do not was unknown.Objective:To determine whether HIV-infected women who received incentives to remain in care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 13 publications
(15 reference statements)
2
56
0
Order By: Relevance
“…Our findings contribute to the scientific literature examining the efficacy of economic interventions in improving HIV treatment adherence [18, 2427], and expand this evidence base to an adolescent population. To our knowledge, this is the first study to utilize a randomized experimental design to assess the longitudinal effects of an economic intervention on HIV viral suppression among adolescents.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our findings contribute to the scientific literature examining the efficacy of economic interventions in improving HIV treatment adherence [18, 2427], and expand this evidence base to an adolescent population. To our knowledge, this is the first study to utilize a randomized experimental design to assess the longitudinal effects of an economic intervention on HIV viral suppression among adolescents.…”
Section: Discussionmentioning
confidence: 53%
“…The published literature has largely focused on poor adults who are living with HIV and includes strategies relating to financial and economic incentives [18, 24], food assistance [18, 25], medication vouchers and subsidies [26, 27], as well as microfinance [26] and entrepreneurial education [27]. By and large, these studies have found significant improvements in treatment adherence among HIV-infected adults.…”
Section: Introductionmentioning
confidence: 99%
“…third 90) among PWLHIV are limited . Yet, in addition to the high rate of loss to follow‐up among PWLHIV , adherence to ART among those retained in care is known to be sub‐optimal, particularly in the postpartum period . In a pooled analysis of 51 studies involving 20,153 PWLHIV mostly from United States, Kenya, South Africa and Zambia, 75.7% of participants had adequate (≥80%) ART adherence during pregnancy compared with 53.0% in the postpartum .…”
Section: Introductionmentioning
confidence: 99%
“…All analyses were adjusted for participant’s age in years, marital status, years of education, gestational age at enrollment, primigravida, disclosure of HIV status, means of arrival at clinic (by foot or other), and a socioeconomic status (SES) index determined using principal components analysis and grouped by quintile. Details of the factor analysis are reported elsewhere (Yotebieng et al, 2016b). …”
Section: Methodsmentioning
confidence: 99%